Conversor c.a.-c.c. isolado de 500W com correção de fator de potência para aplicações aeronáuticas - Gustavo Sathler Zappulla (2023)
The environmental impact of air transportation in the world has led the aviation industry to invest more and more in aircraft electrification. In this context, high-efficiency and high power density are crucial requirements for aircraft electrical systems, since they directly influence fuel consumption and consequently greenhouse gas emissions. This work presents the methodology used for an accurate design of an isolated 500W ac-dc converter for aircraft purposes. With this aim, two main topics are addressed: analysis and measurement of semiconductor losses, which have a major influence on the converter efficiency; and optimization of magnetic devices, which mostly impacts the converter power density. The rated level of efficiency for the proposed converter requires the use of wide bandgap semiconductors. For this reason, a deep analysis on their losses mechanisms is provided, as well as the comparisons between semiconductor dynamic characterisation methods. Moreover, a planar transformer is used to provide the isolation associated with a high level of integration. The topologies Dual-Interleaved Totem-Pole and Dual-Active-Bridge were chosen respectively for power factor correction and galvanic isolation stages. The results of a preliminary design (based on manufacturer datasheets) are provided, together with ones obtained through the experimental characterisation of the devices. This converter has been experimentally implemented and some results are presented in order to evaluate the design.